Piezo1-directed neutrophil extracellular traps regulate macrophage differentiation during influenza virus infection - Yuexin Wang; Qiuli Yang; Yingjie Dong; Likun Wang; Zhiyuan Zhang; Ruiying Niu; Yufei Wang; Yujing Bi; Guangwei Liu (Cell Death and Disease)
Abstract Neutrophils and macrophages are critical for antiviral immunity, but their reciprocal regulatory roles and mechanisms in the response to viral infection remain unclear. Herein, we found that the ion channel Piezo1 directs neutrophil extracellular trap (NET) formation and regulates macrophage functional differentiation in anti-influenza virus immunity. Genetic deletion of Piezo1 in neutrophils inhibited the generation of NETs and M1 macrophage differentiation while driving the development of M2 macrophages during viral infection. Piezo1-directed neutrophil NET DNA directly regulates macrophage differentiation in vitro and in vivo. Mechanistically, neutrophil Piezo1 deficiency inhibited NET DNA production, leading to decreased TLR9 and cGAS-STING signalling activity while inducing reciprocal differentiation from M1 to M2 macrophages. In addition, Piezo1 integrates magnesium signalling and the SIRT2-hypoxia-inducible factor-1 alpha (HIF1α)-dependent pathway to orchestrate reciprocal M1 and M2 macrophage lineage commitment through neutrophil-derived NET DNA. Our studies provide critical insight into the role of neutrophil-based mechanical regulation of immunopathology in directing macrophage lineage commitment during the response to influenza virus infection.